Isolation and Biological Characterization of Highly Potent Tributyltin Chloride Resistant Bacteria Alcaligenes sp. swo Strain Sd from Goa, India: Characterization and Resistance Mechanisms of Tributyltin Chloride Resistant Bacteria in Marine Water of Goa (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Water samples were collected from various sampling sites surrounding the ship building industries in Goa and plated on Zobell marine agar (ZMA), Nutrient agar (NA) and Mineral salt medium agar (MSMA) containing 0.1 mM tributyltin chloride (TBTC). The physico-chemical characteristics of the water samples were determined. The total viable counts of bacteria ranged from 58 × 102 cfuml in MSMA+TBTC to 40.6 × 106 cfuml in ZMA+TBTC. This clearly indicates predominance of TBTC tolerant and degrading bacterial isolates in marine water of Goa. Although, several highly TBTC tolerant bacterial isolates were screened, one bacterial strain tolerated up to 7 mM TBTC and showed prominent growth in MSM supplemented upto 5mM TBTC. This clearly indicates that TBTC resistant bacterial isolate utilizes TBTC as a sole carbon source. Based on morphological, biochemical, and molecular characteristics (16S rDNA Sequence taxonomic phenogram) this TBTC resistant isolate have been grouped in Al caligenes sp. swo.